2006
DOI: 10.1007/s00259-006-0191-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeted functional imaging of estrogen receptors with 99mTc-GAP-EDL

Abstract: Cellular or tumor uptake of (99m)Tc-GAP-EDL occurs via an ER-mediated process. (99m)Tc-GAP-EDL is a useful agent for imaging functional ER(+) disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Further, the values for DES and dienestrol themselves are consistent with a preferential inhibition of the MDA non-estrogen cancer cell line. DES is effective against estrogen receptor positive (ER+) tumors such as the MCF-7 cell line [37,38,39,40,41,42,43,44,45,46]. It is possible that some of the drug is bound to the estrogen receptors in the MCF-7 cells making the drug unavailable to act within the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the values for DES and dienestrol themselves are consistent with a preferential inhibition of the MDA non-estrogen cancer cell line. DES is effective against estrogen receptor positive (ER+) tumors such as the MCF-7 cell line [37,38,39,40,41,42,43,44,45,46]. It is possible that some of the drug is bound to the estrogen receptors in the MCF-7 cells making the drug unavailable to act within the cell.…”
Section: Resultsmentioning
confidence: 99%
“…99m Tc-DTPA-estradioldemonstrated a KD much higher than typically reported values of estradiol itself (0.1-1.0 nM) [25,26], but was comparable to the affinity of a similar estrogen receptor (11 ± 1.5) nM [10]. Further, GAP-EDL was found to accumulate into ER+ 13762 (rat mammary carcinoma) tumors with a tumor-to-muscle ratio of 7.92 ± 0.56 at 4 h [21]; and 99m Tc-estradiol-pyridin-2-yl has been shown to target MCF-7 tumors with a tumor-to-muscle ratio of 5.67 ± 1.06 at 3 h post-injection [10].…”
Section: Accepted Manuscriptmentioning
confidence: 46%
“…The chelator DTPA was introduced to estradiolvia DTPA anhydride under mild conditions of pH and temperatures. Previous studies have suggested that 3-acetonitrile estradiol could be produced via an ER-mediated process, and that 99m Tc-labeled estradiol could be a useful agent for imaging ER status [21,22]. Compared with previous estradiol probes, DTPA-estradiol is a small molecule with a suitable molecular weight.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…PET/CT and SPECT/CT agents show high specific activities because they are made through a nuclear transformation and use carrier free forms of isotopes. Moreover, PET/CT and SPECT/CT chelator-based agents do not produce detectable pharmacologic effects but provide important information concerning the characterization of varieties diseases, such as vascular angiogenesis [4][5][6], hypoxia [7][8][9], apoptosis [10][11], cellular signaling and transcriptional activity [12][13][14]. PET/CT and SPECT/CT may assist in the determination of optimal therapeutic dosing, differential diagnosis between inflammation/infection and recurrence, sensitive or resistant to treatment response, grading of tumors, and the prediction of treatment response by selecting patient who may or may not respond to therapy.…”
Section: Importance Of Nuclear Molecular Imaging In Oncologymentioning
confidence: 99%